Big Data Framework for Auditing Process - P. Yudowati, Siska; Alamsyah, Andry (International Journal of Engineering and Technology, 2018)
An audit of financial report is a review of the organization financial statement that carried out by the independent and professional in their field which is the Auditor. The Big Data methodology offered a different approach compared to the current audit procedure, which mostly using manual process. Big Data equipped with learning capabilities and automation process in order to achieve better and faster result. Another advantage of using Big Data methodology is to provide comprehensive and multi-dimensional view of the problem. This paper provides a framework to incorporated auditing process and Big Data approach, specifically by mapping the internal and external data source to one of audit process stage, which is risk assessment process. Â Â